Methods of work of the commander of a military part of National Guards of Ukraine by development to a plan of special operation in view of stressful circumstances - Yermoshin, М. О.; Oleshchenko, О. А.; Poberezhnyi, А. А. (Honor and Law, 2019)
The process of designing a special operation for the military unit of the National Guard of Ukraine with consideration of stressful circumstances is considered.